Empowerment of Super Village Chicken Breeder Groups in Baruga District - Farra Sasmita; La Haruddin; Hajar; Rustan Ari (PT FORMOSA CENDEKIA GLOBAL, 2022)
Watubangga Subdistrict is one of the subdistricts in Baruga District, Kendari City which has a very potential area for the development of livestock businesses, specifically the super free-range chicken business. The service aims to provide understanding to the Mahika Mandiri livestock group regarding Strengthening Capacity and Group Dynamics, Maintenance Management, Housing and Sanitation, and Technical Guidance on Making Hatchery Machines and Their Use with the duration of the service from September to October 2022. The results of the service can provide benefits regarding strengthening capacity and group dynamics, changing the way farmers manage maintenance, housing and sanitation, and livestock groups that are members of the Mahika Mandiri group can make hatching machines and how to use them.